THE REQUIREMENTS OF SOCIETY: THE IMPERATIVE FOR JOURNALISM AND PUBLIC RELATIONS - Fedotova, L.N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2018)
The article examines the conceptual framework that describes the interaction of public relations and journalism with society at large by using the terms “corporate social responsibility” and “social mission”. Public attention to this problem is inseparable from the increased importance in the public opinion of the place and role of business in the life of society and the responsibilities of business. In parallel to this process there was an increasing demand for adequate information support of business processes, in particular, for public relations - its place and role, as well as for journalism, as a mirror of the main events, processes, activities of political and economic actors.